Germ cell neoplasia in situ (GCNIS): evolution of the current nomenclature for testicular pre‐invasive germ cell malignancy. Issue 1 (12th April 2016) - Berney, Daniel M; Looijenga, Leendert H J; Idrees, Muhammad; Oosterhuis, J Wolter; Rajpert‐De Meyts, Ewa; Ulbright, Thomas M; Skakkebaek, Niels E
Abstract : The pre‐invasive lesion associated with post‐pubertal malignant germ cell tumours of the testis was first recognized in the early 1970s and confirmed by a number of observational and follow‐up studies. Until this year, this scientific story has been confused by resistance to the entity and disagreement on its name. Initially termed 'carcinoma in situ ' (CIS), it has also been known as 'intratubular germ cell neoplasia, unclassified' (IGCNU) and 'testicular intraepithelial neoplasia' (TIN). In this paper, we review the history of discovery and controversy concerning these names and introduce the reasoning for uniting behind a new name, endorsed unanimously at the World Health Organization (WHO) consensus classification 2016: germ cell neoplasia in situ (GCNIS).